Post-transcriptional control of miRNA abundance in Arabidopsis - Ren, Guodong (Landes Bioscience, 2012)
MicroRNAs (miRNAs) are a class of small non-coding RNAs (small RNAs) that are 20–24nt in length and predominantly repress gene expression at post-transcriptional levels. They regulate many biological processes including development, metabolism and physiology. Numerous studies have revealed that the steady-state levels of miRNA are under sophisticated control to ensure their proper function. In this review, we summarize recent advances on regulation of miRNA processing and stability in plants.